2011
DOI: 10.1371/journal.pone.0016198
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Secretion Induced by Titanium Dioxide Nanoparticles

Abstract: Nanoparticle (NP) exposure has been closely associated with the exacerbation and pathophysiology of many respiratory diseases such as Chronic Obstructive Pulmonary Disease (COPD) and asthma. Mucus hypersecretion and accumulation in the airway are major clinical manifestations commonly found in these diseases. Among a broad spectrum of NPs, titanium dioxide (TiO2), one of the PM10 components, is widely utilized in the nanoindustry for manufacturing and processing of various commercial products. Although TiO2 NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 48 publications
3
58
1
Order By: Relevance
“…The question of whether TiO 2 NPs can trigger a similar process is unclear. Our experiments confirmed that [Ca 2+ ] C failed to increase significantly when cells were treated with TiO 2 NPs in Ca 2+ -free Hanks' solution (Figure 2B) or blocked with CdCl 2 (a general Ca 2+ channel blocker) (Figure 2C) [17]. We then demonstrated that TiO 2 NPs can activate L-type voltage-gated Ca 2+ channels on mast cells, allowing extracellular Ca 2+ influx into the cytosol (Figure 2D and 2E).…”
Section: Discussionsupporting
confidence: 72%
“…The question of whether TiO 2 NPs can trigger a similar process is unclear. Our experiments confirmed that [Ca 2+ ] C failed to increase significantly when cells were treated with TiO 2 NPs in Ca 2+ -free Hanks' solution (Figure 2B) or blocked with CdCl 2 (a general Ca 2+ channel blocker) (Figure 2C) [17]. We then demonstrated that TiO 2 NPs can activate L-type voltage-gated Ca 2+ channels on mast cells, allowing extracellular Ca 2+ influx into the cytosol (Figure 2D and 2E).…”
Section: Discussionsupporting
confidence: 72%
“…We observed increased intracellular Ca 2+ in the cells exposed to SiO 2 NPs, SWCNTs and ufCB. Nanomaterials have been shown to accelerate extracellular Ca 2+ influx via compromised cell membrane integrity [68-70]. Nanosized titanium dioxide has been shown to increase levels of cytosolic Ca 2+ in human bronchial ChaGo-K1 epithelial cells [68].…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials have been shown to accelerate extracellular Ca 2+ influx via compromised cell membrane integrity [68-70]. Nanosized titanium dioxide has been shown to increase levels of cytosolic Ca 2+ in human bronchial ChaGo-K1 epithelial cells [68]. To explore if nanomaterials mediated Ca 2+ influx led to PAD-dependent protein citrullination, human epithelial A549 and phagocytic THP-1 cells were exposed to SWCNTs, ufCB and SiO 2 NPs in the presence of a Ca 2+ channel blocker.…”
Section: Discussionmentioning
confidence: 99%
“…A sustained elevation of Ca 2+ was achieved by inducing the release of Ca 2+ from the endoplasmic reticulum leading to histamine secretion. TiO 2 NPs also stimulate mucin secretion in epithelial cells by inducing extracellular Ca 2+ influx and calcium release from the endoplasmic reticulum (Chen et al, 2011). Intracellular Ca 2+ increase is also involved in the inhibition of cell proliferation by Ag NPs (Asharani et al, 2009).…”
Section: 3 Other Cellular Mechanisms Induced By Nanomaterialsmentioning
confidence: 99%